PERBANDINGAN UNJUK KERJA RESIN PENUKAR ION BASA KUAT DOWEX MARATHON A DENGAN PUROLITE PADA PROSES PEMURNIAN BIOGAS SKALA PILOT PLANT - Dyah Retno Sawitri; M. Haekal Arkan; Endhika Yasa Pradikta; M. Khoirul Ummam; Anies Mutiari (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Adsorption of carbon dioxide is a vital process in biogas purification. A previous study has narrowed down the choice of ion exchange resins for the adsorption process into two commercial resins, Dowex Marathon A, and Purolite. Dowex Marathon A boasts the advantage of having no need of any pretreatments to use. Purolite, although needing pretreatment before usage, costs only roughly a third of Dowex Marathon A. The objective of the study is to decide on which resin is best suited to commercially produce biogas free from pollutants, most of which is carbon dioxide. Both resins at their fresh state were tested for durability by checking on levels of carbon dioxide content at set time intervals. Results suggest the Purolite resin to be more durable than the Dowex Marathon A resin. Data of gas passing through Dowex showed relatively high concentration of CO2 after 10 minutes of operation. While Purolite showed its first signs of CO2 after 20 minutes of operation. Further tests are conducted to compare fresh and regenerated Pirolite resins. Comparison between fresh and postregeneration Purolite showed relatively consistent results where the regenerated resin showed its first signs of CO2 after 25 minutes.